The domestic pig as a translational model of hyperoxaluria: a pilot study of acute and chronic sodium oxalate infusion - Jacek, Tomasz; Szkopek, Dominika; Wychowański, Piotr; Donaldson, Janine; Zaworski, Kamil; Strutyński, Mariusz; Kirko, Siarhei; Prykhodko, Olena; Fedkiv, Olexandr; Pierzynowski, Stefan G.; Pierzynowska, Kateryna (Frontiers in Physiology, 2026)
The purpose of this pilot study was to develop and characterize an in vivo porcine model of hyperoxaluria using intravenous infusion of sodium oxalate (NaOx). Two experimental regimens were developed to replicate acute and follow up chronic hyperoxaluria. In the acute model, 3 different doses of 1% NaOx were administered over 15 h, resulting in a dose-dependent increase in plasma oxalate concentration (Cmax: 42.4–122.4 µM) and transient hyperoxaluria, with a return to baseline values 6–8 h after stopping the infusion of NaOx solution. In the chronic model, repeated infusions of NaOx for 7–11 days directly after acute tests led to persistent hyperoxalemia (up to 302.4 µM), clinical deterioration and dose-dependent calcium oxalate (CaOx) deposits in renal tissue (1.85%–9.55% of renal surface area), consistent with impaired renal function. The model represents the key clinical features of both rapidly inducible and reversible hyperoxalemia and hyperoxaluria, as well as the progressive nephrocalcinosis. Due to the physiological similarity between pigs and humans, the proposed porcine model could be considered as a quick and valuable tool for studying the pathophysiology of oxalate excess and testing the efficacy of new therapies to counteract its toxicity.